2002
DOI: 10.1111/1468-2435.00187
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the Fittest: Russian Immigrant Teachers Speak about Their Professional Adjustment in Israel

Abstract: This qualitative study explores the determinants of occupational integration among recent immigrants whose profession is culturally and linguistically dependent. It compares personal accounts of 36 former Soviet school teachers of math and physics, of whom 20 succeeded in regaining their occupation in Israel and 16 left teaching for different reasons. Analysis of the interviews shows that, even in a society committed to the goal of professional integration of the immigrants, cultural barriers to successful wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 19 publications
4
42
0
10
Order By: Relevance
“…In Israel, certain participants in Remennick's (2002) study reported having conflicts with their Israeli colleagues. The teaching personnel of Russian origin perceived that their Israeli colleagues considered them a threat to their jobs and kept a distance.…”
Section: Professional Integration Problems Specific To Immigrant Teacmentioning
confidence: 99%
See 4 more Smart Citations
“…In Israel, certain participants in Remennick's (2002) study reported having conflicts with their Israeli colleagues. The teaching personnel of Russian origin perceived that their Israeli colleagues considered them a threat to their jobs and kept a distance.…”
Section: Professional Integration Problems Specific To Immigrant Teacmentioning
confidence: 99%
“…Problems of access to employment could also be attributed to linguistic and cultural barriers (Beynon, Ilieva, & Dichoupa, 2004;Cruickshank, 2004;Elbaz-Luwisch, 2004;Maureen, 1992;Gordon, 1996;Hutchison, 2005;Myles, Cheng, & Wang, 2006;Phillion, 2003;Reid, 2005;Remennick, 2002;Schmidt, 2010). Not mastering the language and the culture of the country could hamper access to employment (Dakin, 1971).…”
Section: Professional Integration Problems Specific To Immigrant Teacmentioning
confidence: 99%
See 3 more Smart Citations